The Spring Heat Source Over the Qinghai–Tibetan Plateau Linked With the Winter Warm Arctic–Cold Siberia Pattern Impacting Summer Drought in China - Yang, Yumeng; Zhao, Liang; Shen, Xinyong; Xiao, Ziniu; Li, Qingquan (Frontiers in Earth Science, 2022)
The atmospheric heat source over the Qinghai–Tibetan Plateau (QTP) in spring has an important impact on the climate of the surrounding regions. However, there have been few systematic studies of the dominant mode of the heat source and the cross-seasonal connections with the preceding winter and following summer. Using a distinct empirical orthogonal function (DEOF) decomposition method, we obtained the leading mode of the spring heat source over the QTP and the surrounding regions and analyzed its precursors in the previous winter and lagging effects in the following summer. Our results show that the first mode (DEOF1) was characterized by a warm plateau and cold surrounding regions. The positive phase was significantly associated with the warm Arctic–cold Siberia (WACS) pattern (r = 0.39, p = 0.01) and the La Niña-like SST anomaly in the Pacific in the preceding winter and the following East Asian subtropical summer monsoon (r = –0.44, p = 0.01), resulting in a widespread drought in China during the following summer. The cold anomaly in Siberia and the warm anomaly at mid- to low latitudes in winter associated with the WACS pattern coincide with the DEOF1 mode of the heat source over the QTP and its surroundings through change of meridional temperature gradient and wave-flow interactions. A mid-latitude wave train excited by the WACS and the thermal difference in the meridional direction of the spring DEOF1 mode caused high-pressure anomalies over the QTP and the mid-latitude region of East Asia, influencing central and eastern China. This anomaly was not conducive to the northward advancement of the East Asian summer monsoon, resulting in drought in most of China in spring and summer. The cross-seasonal relationship between the main mode of the spring heat source on the QTP and the preceding winter WACS pattern and the following East Asian summer monsoon can be used as a reference in climate prediction studies.